Effect Of Mentha Piperita On Biochemical Parameters Of Broilers Fed Ochratoxin - Nayak, Anju; Joseph, E.; Nayak, S.; Swamy , M.; Baghel , R.P.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A trial was conducted to study the effect of Mentha piperita on broilers fed ochratoxin. The results of the present study reveals that feeding of ochratoxin at both the levels (2 and 4 ppm) significantly (P<0.05)reduced the level of serum total protein and albumin and significantly increased serum creatinine, ALP, AST and ALT. whereas no significant change observed due to administration of M.Piperita at both the levels (2and 4 g/kg feed). There was non significant increase in serum total protein in group VI.